IoT in Arctic Tourism - A Case-study of the Tourist Information Office in Narvik - Mustafa, Ayah; Noureddine, Rami; Thordarson, Diana (FRUCT Oy, 2022)
The internet of things (IoT) provides linkage between physical objects and their virtual counterparts so that things can be done much faster, cheaper, and in a more convenient manner for users. IoT is an important element in the smart tourism city, a concept based on data sharing between the public, private sectors, and visitors of the smart city. In such a setting, tourists and residents of the smart destination digitally and physically share their experiences to enhance their experiences. This paper discusses the potential applications and impacts of IoT in smart tourism. In addition, the paper further investigates a study-case conducted at the Tourist Information Office in the Narvik Region located in Northern Norway. Four different IoT challenges are represented with the possible solutions and advancements. The study-case aims to provide better customer service, while still maintaining a high level of technological ease and common usability. Even though these examples are directly related to a single tourist information, the same applications may be applied to other places in the world by following the same systems.